Low-smoke halogen-free flame-retardant marine power cable material and preparation method thereof

By complexing the modified low-density polyethylene with zinc salt solution to form a zinc hydroxide/glucose-based carbon layer, combining graphene aerogel and dimolyte trioxide, the problems of toxic gas release and poor oxidation resistance of traditional cable materials during combustion are solved, and low smoke, halogen-free flame retardant and mechanical properties are improved.

CN120574449APending Publication Date: 2025-09-02YANGZHOU GUANGMING CABLE CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510972371.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-15
Publication Date
2025-09-02

AI Technical Summary

Technical Problem

Traditional halogen-containing flame-retardant wires and cables produce toxic gases and corrosive smoke when burned, which endangers human health and pollutes the environment. The existing antioxidants are prone to migration and precipitation, resulting in poor oxidation resistance and waterproofing performance of the cable.

Method used

Modified low-density polyethylene and zinc salt solution are used to form zinc hydroxide/glucose-based carbon, and mixed powder with high-density polyethylene as an intermediate layer, forming a solid carbon layer by pressurized heat treatment, combining graphene aerogel and dimolyte trioxide to improve flame retardant performance, and using natural olive phenol antioxidants to enhance mechanical properties.

Benefits of technology

Low smoke, halogen-free flame retardant is achieved, which improves the mechanical and flame retardant properties of cable materials, slows down the combustion process, reduces the combustion temperature rise rate, and enhances the overall performance of the cable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005500363610000091
    Figure BDA0005500363610000091
  • Figure BDA0005500363610000101
    Figure BDA0005500363610000101
Patent Text Reader

Abstract

The invention discloses a low-smoke halogen-free flame-retardant marine power cable material and a preparation method thereof, and relates to the technical field of cable materials. Modified glucose is grafted with low-density polyethylene and soaked in a zinc salt solution to form a complex, and the complex is combined with high-density polyethylene mixed powder and subjected to pressurized heat treatment. Glucose is pyrolyzed into carbon through heat treatment, zinc ions form zinc hydroxide attached to the surface of carbon, and the mechanical performance of the material can be effectively improved. Meanwhile, zinc hydroxide and glucosyl carbon act together, so that the flame retardant property is improved. The upper layer and the lower layer are compounded by high-density polyethylene, polystyrene and graphene aerogel, hardness and softness are combined, HDPE maintains toughness, PS enhances rigidity, graphene optimizes overall mechanical properties, and the sheath material with excellent mechanical properties is obtained. The graphene-dominated flame-retardant mechanism is combined with the heat insulation performance and the barrier effect of aerogel, escape of polystyrene decomposition products is inhibited, and the flame-retardant performance is optimized through molybdenum sesquioxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of cable materials, in particular to a low-smoke, halogen-free, flame-retardant shipboard power cable material and a preparation method thereof. Background Art

[0002] Traditional halogen-containing flame-retardant wires and cables present numerous problems during use. First, these materials produce carcinogens such as dioxins during combustion, posing a serious threat to human health. Second, they release large amounts of toxic smoke and corrosive gases during combustion, which not only accelerates asphyxiation of personnel at the fire scene but also complicates rescue efforts. Furthermore, these corrosive gases can corrode electrical equipment at and near the fire scene, rendering them useless and causing economic losses. More seriously, halogen flame retardants accumulate toxicity and can generate carcinogens during production, transportation, storage, application, and recycling of waste products. These issues contribute to environmental pollution and pose a potential threat to human health. Therefore, the market urgently needs new, environmentally friendly cable materials to replace traditional halogen-containing flame-retardant cable materials.

[0003] In daily life, wires and cables generally use high-density polyethylene (HDPE) with good softness, ductility, electrical insulation and transparency as the inner sheath, but its oxidation resistance is poor and it is easy to crack under the action of thermal oxidative aging. In the existing technology, its oxidation resistance is often improved by adding antioxidants, but conventional antioxidants have a small molecular weight and cannot participate in the cross-linking and curing reaction. They are easy to migrate and precipitate, resulting in poor oxidation resistance of wires and cables. In addition, the existing HDPE has poor waterproof performance and poor solvent resistance, and corrosive media such as water molecules can easily enter the interior of the HDPE material. Summary of the Invention

[0004] The object of the present invention is to provide a low-smoke halogen-free flame-retardant shipboard power cable material and a preparation method thereof, so as to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solution: a low-smoke, halogen-free, flame-retardant shipboard power cable material, comprising, by weight, 100 to 140 parts of modified low-density polyethylene powder, 280 to 340 parts of high-density polyethylene powder, 20 to 30 parts of molybdenum trioxide, 5 to 8 parts of urea, 15 to 30 parts of antioxidant, 80 to 120 parts of polystyrene powder, 5 to 8 parts of lubricant, and 40 to 60 parts of graphene aerogel powder. The preparation method of the modified low-density polyethylene is as follows: after pre-irradiation, the low-density polyethylene is immersed in a modified glucose solution, taken out and dried, and then immersed in a zinc salt solution, and taken out and dried.

[0006] Furthermore, the particle sizes of the polystyrene powder, low-density polyethylene powder and high-density polyethylene powder are 53 to 213 μm.

[0007] Furthermore, the low-density polyethylene powder has a melt index of 1.85-1.93 g / 10 min and a density of 0.915-0.93 g / cm 3 .

[0008] Furthermore, the density of the high-density polyethylene powder is 0.940 to 0.976 g / cm 3 , the crystallinity is 50% to 60%.

[0009] Furthermore, the specific steps of the pre-irradiation are: in an air atmosphere, the low-density polyethylene powder is pre-irradiated with beta rays on an electron accelerator device, with an irradiation dose of 5 kGy.

[0010] Furthermore, the preparation method of the modified glucose is as follows: 14-20 g of glucose and 50-60 mL of methanol are stirred at 65°C to completely dissolve them, then 1-5 g of 3-butene-1-amine and 0.1 mL of glacial acetic acid are added, and the mixture is reacted for 2 hours to precipitate a large amount of white precipitate, which is filtered, and the filter cake is washed three times with anhydrous methanol and dried at 40°C for 12 hours.

[0011] Furthermore, the relative molecular mass of the polystyrene is 3000 g / mol.

[0012] Furthermore, the lubricant is at least one of silicone oil, magnesium stearate, paraffin, and PE wax.

[0013] Furthermore, the modified glucose solution is a 50-60 wt% modified glucose aqueous solution at 80°C.

[0014] Furthermore, the antioxidant is a combination of natural olive phenol extract and antioxidant 168 in a weight ratio of 1:2.

[0015] Furthermore, a method for preparing a low-smoke halogen-free flame-retardant marine power cable material comprises the following preparation steps:

[0016] (1) Modified low-density polyethylene powder and urea are mixed uniformly in proportion, ground at 300-500 rpm for 10-15 minutes, and 1 / 3 of the weight of antioxidant is added and mixed uniformly to obtain an intermediate layer powder;

[0017] (2) 1 / 2 mass of graphene aerogel powder (prepared with reference to CN201810033667.X) and 1 / 2 mass of molybdenum trioxide were mixed evenly, ground at 300-500 rpm for 10-15 min, and then 1 / 3 mass of antioxidant, 2 / 3 mass of polystyrene, 1 / 2 mass of lubricant, and 1 / 2 mass of high-density polyethylene powder were added in sequence and mixed thoroughly to obtain an upper layer of powder; the remaining materials were used to prepare a lower layer of powder according to the above process;

[0018] (3) The lower layer powder, the middle layer powder and the upper layer powder are respectively loaded into the mold in order, the three mixed powders are not mixed, pressurized and sintered, and demolded to obtain low-smoke halogen-free flame-retardant marine power cable material.

[0019] Furthermore, the pressurization pressure in step (3) is 3-35 MPa, and the sintering temperature is: first heated to 135°C, kept warm for 1 hour, then heated to 150°C, kept warm for 2 hours, and finally heated to 180-200°C, kept warm for 1 hour.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The present invention adopts modified glucose grafted low-density polyethylene as raw material, soaks in zinc salt solution, relies on glucose to complex with zinc ions, and uses it as an intermediate layer, and is mixed with upper and lower layers of high-density polyethylene powder, and is subjected to pressurized heat treatment. The heat treatment temperature causes glucose to be pyrolyzed into carbon, and the heat treatment temperature is relatively low, and the zinc ions form zinc hydroxide and adhere to the carbon surface. Due to the early grafting treatment, the zinc hydroxide / glucose-based carbon is uniformly dispersed in the polyethylene matrix, which plays a reinforcing and filling role on the material. At the same time, this treatment method reduces the interface defects between the filler and the matrix, enhances the interaction between the two, and improves the mechanical properties of the cable material. In addition, in the event of fire or high temperature, the zinc hydroxide will decompose and absorb a large amount of heat energy when heated, reducing the temperature rise rate of the polyethylene cable material when burning, slowing down the thermal decomposition and combustion process of the material, and forming a carbonization catalyst zinc oxide, which participates in the carbonization process with the glucose-based carbon, synergistically making the carbon layer more solid and dense, and improving the flame retardant properties of the cable material. DETAILED DESCRIPTION

[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0023] Example 1

[0024] A low-smoke, halogen-free, flame-retardant shipboard power cable material, comprising, by weight, 100 parts of modified low-density polyethylene powder, 280 parts of high-density polyethylene powder, 20 parts of molybdenum trioxide, 5 parts of urea, 15 parts of an antioxidant, 80 parts of polystyrene powder, 5 parts of silicone oil, and 40 parts of graphene aerogel powder; the antioxidant is a combination of a natural olive phenol extract and antioxidant 168 in a weight ratio of 1:2; the polystyrene powder has a particle size of 213 μm, the low-density polyethylene powder has a particle size of 53 μm, and the high-density polyethylene powder has a particle size of 213 μm;

[0025] The preparation method of the modified low-density polyethylene is:

[0026] (1) 14 g of glucose and 50 mL of methanol were stirred at 65°C until completely dissolved, and then 1 g of 3-butene-1-amine and 0.1 mL of glacial acetic acid were added. The mixture was reacted for 2 h to precipitate a large amount of white precipitate. The precipitate was filtered and the filter cake was washed three times with anhydrous methanol and dried at 40°C for 12 h to obtain modified glucose.

[0027] (2) In an air atmosphere, low-density polyethylene powder is pre-irradiated with beta rays on an electron accelerator device at an irradiation dose of 5 kGy. Modified glucose is prepared into a 50 wt% modified glucose aqueous solution at 80°C, and the pre-irradiated low-density polyethylene powder is completely immersed in the solution for 1 hour, taken out and dried, and then completely immersed in a zinc salt solution. The mass ratio of zinc acetate to deionized water in the zinc salt solution is 0.5 g:40 mL. After soaking for 1 hour, the powder is taken out and dried;

[0028] The preparation method of the low-smoke halogen-free flame-retardant shipboard power cable material is as follows:

[0029] (1) Modified low-density polyethylene powder and urea are mixed uniformly in proportion, ground at 300 rpm for 10 min, 1 / 3 of the weight of antioxidant is added, and mixed uniformly to obtain an intermediate layer powder;

[0030] (2) 1 / 2 mass of graphene aerogel powder and 1 / 2 mass of molybdenum trioxide were mixed evenly, ground at 300 rpm for 10 min, and then 1 / 3 mass of antioxidant, 2 / 3 mass of polystyrene, 1 / 2 mass of lubricant, and 1 / 2 mass of high-density polyethylene powder were added in sequence and mixed thoroughly to obtain an upper layer of powder; the remaining materials were used to prepare a lower layer of powder according to the above process;

[0031] (3) The lower layer powder, the middle layer powder and the upper layer powder are loaded into the mold in order. The three mixed powders are not mixed. The pressurization pressure is maintained at 3 MPa. The temperature is first raised to 135 ° C and kept warm for 1 hour. Then the temperature is raised to 150 ° C and kept warm for 2 hours. Finally, the temperature is raised to 180 ° C and kept warm for 1 hour to obtain low-smoke halogen-free flame-retardant shipboard power cable material.

[0032] Example 2

[0033] A low-smoke, halogen-free, flame-retardant shipboard power cable material, comprising, by weight, 110 parts of modified low-density polyethylene powder, 300 parts of high-density polyethylene powder, 22 parts of molybdenum trioxide, 7 parts of urea, 15 parts of an antioxidant, 80 parts of polystyrene powder, 5 parts of magnesium stearate, and 43 parts of graphene aerogel powder; the particle size of the polystyrene powder, low-density polyethylene powder, and high-density polyethylene powder is 88 μm; the antioxidant is a combination of a natural olive phenol extract and antioxidant 168 in a weight ratio of 1:2;

[0034] The preparation method of the modified low-density polyethylene is:

[0035] (1) 18 g of glucose and 50 mL of methanol were stirred at 65°C until completely dissolved, and then 3 g of 3-butene-1-amine and 0.1 mL of glacial acetic acid were added. The mixture was reacted for 2 h to precipitate a large amount of white precipitate. The precipitate was filtered and the filter cake was washed three times with anhydrous methanol and dried at 40°C for 12 h to obtain modified glucose.

[0036] (2) In an air atmosphere, low-density polyethylene powder is pre-irradiated with beta rays on an electron accelerator device at an irradiation dose of 5 kGy. Modified glucose is prepared into a 52 wt% modified glucose aqueous solution at 80°C, and the pre-irradiated low-density polyethylene powder is completely immersed in the solution for 1 hour, removed from the solution for drying, and then completely immersed in a zinc salt solution in which the mass ratio of zinc acetate to deionized water is 1.5 g:40 mL. After soaking for 1 hour, the solution is removed from the solution for drying;

[0037] The preparation method of the low-smoke halogen-free flame-retardant shipboard power cable material is as follows:

[0038] (1) Modified low-density polyethylene powder and urea are mixed uniformly in proportion, ground at 30 rpm for 15 min, 1 / 3 of the weight of antioxidant is added, and mixed uniformly to obtain an intermediate layer powder;

[0039] (2) 1 / 2 mass of graphene aerogel powder and 1 / 2 mass of molybdenum trioxide were mixed evenly, ground at 300 rpm for 15 min, and then 1 / 3 mass of antioxidant, 2 / 3 mass of polystyrene, 1 / 2 mass of lubricant, and 1 / 2 mass of high-density polyethylene powder were added in sequence and mixed thoroughly to obtain an upper layer of powder; the remaining materials were used to prepare a lower layer of powder according to the above process;

[0040] (3) The lower layer powder, the middle layer powder and the upper layer powder are loaded into the mold in order. The three mixed powders are not mixed. The pressurization pressure is maintained at 6 MPa. The temperature is first raised to 135 ° C and kept warm for 1 hour. Then the temperature is raised to 150 ° C and kept warm for 2 hours. Finally, the temperature is raised to 180 ° C and kept warm for 1 hour to obtain low-smoke halogen-free flame-retardant shipboard power cable material.

[0041] Example 3

[0042] A low-smoke, halogen-free, flame-retardant shipboard power cable material, comprising, by weight, 120 parts of modified low-density polyethylene powder, 300 parts of high-density polyethylene powder, 25 parts of molybdenum trioxide, 5 parts of urea, 22 parts of an antioxidant, 100 parts of polystyrene powder, 8 parts of paraffin wax, and 50 parts of graphene aerogel powder; the antioxidant is a combination of a natural olive phenol extract and antioxidant 168 in a weight ratio of 1:2;

[0043] The preparation method of the modified low-density polyethylene is:

[0044] (1) 20 g of glucose and 60 mL of methanol were stirred at 65°C until completely dissolved, and then 5 g of 3-butene-1-amine and 0.1 mL of glacial acetic acid were added. The mixture was reacted for 2 h to precipitate a large amount of white precipitate. The precipitate was filtered and the filter cake was washed three times with anhydrous methanol and dried at 40°C for 12 h to obtain modified glucose.

[0045] (2) In an air atmosphere, low-density polyethylene powder is pre-irradiated with beta rays on an electron accelerator device at an irradiation dose of 5 kGy, and modified glucose is prepared into a 55 wt% modified glucose aqueous solution at 80° C. The pre-irradiated low-density polyethylene powder is completely immersed in the modified glucose aqueous solution for 1 hour, removed from the solution for drying, and then completely immersed in a zinc salt solution in which the mass ratio of zinc acetate to deionized water is 2.5 g:40 mL. After soaking for 1 hour, the solution is removed from the solution for drying. The particle size of the polystyrene powder is 53 μm, the particle size of the low-density polyethylene powder is 88 μm, and the particle size of the high-density polyethylene powder is 88 μm.

[0046] The preparation method of the low-smoke halogen-free flame-retardant shipboard power cable material is as follows:

[0047] (1) Modified low-density polyethylene powder and urea are mixed uniformly in proportion, ground at 400 rpm for 12 min, 1 / 3 of the weight of antioxidant is added, and mixed uniformly to obtain an intermediate layer powder;

[0048] (2) 1 / 2 mass of graphene aerogel powder and 1 / 2 mass of molybdenum trioxide were mixed evenly, ground at 400 rpm for 12 min, and then 1 / 3 mass of antioxidant, 2 / 3 mass of polystyrene, 1 / 2 mass of lubricant, and 1 / 2 mass of high-density polyethylene powder were added in sequence and mixed thoroughly to obtain an upper layer of powder; the remaining materials were used to prepare a lower layer of powder according to the above process;

[0049] (3) The lower layer powder, the middle layer powder and the upper layer powder are loaded into the mold in order, and the three mixed powders are not mixed. The pressurization pressure is maintained at 10 MPa, and the temperature is first raised to 135 ° C, kept warm for 1 hour, then raised to 150 ° C, kept warm for 2 hours, and finally raised to 200 ° C, kept warm for 1 hour to obtain low smoke halogen-free flame retardant shipboard power cable material.

[0050] Example 4

[0051] A low-smoke, halogen-free, flame-retardant shipboard power cable material, comprising, by weight, 140 parts of modified low-density polyethylene powder, 300 parts of high-density polyethylene powder, 30 parts of molybdenum trioxide, 8 parts of urea, 30 parts of an antioxidant, 120 parts of polystyrene powder, 8 parts of PE wax, and 60 parts of graphene aerogel powder; the particle size of the polystyrene powder, low-density polyethylene powder, and high-density polyethylene powder is 213 μm; the antioxidant is a combination of a natural olive phenol extract and antioxidant 168 in a weight ratio of 1:2;

[0052] The preparation method of the modified low-density polyethylene is:

[0053] (1) 20 g of glucose and 60 mL of methanol were stirred at 65°C until completely dissolved, and then 5 g of 3-butene-1-amine and 0.1 mL of glacial acetic acid were added. The mixture was reacted for 2 h to precipitate a large amount of white precipitate. The precipitate was filtered and the filter cake was washed three times with anhydrous methanol and dried at 40°C for 12 h to obtain modified glucose.

[0054] (2) In an air atmosphere, low-density polyethylene powder is pre-irradiated with beta rays on an electron accelerator device at an irradiation dose of 5 kGy. Modified glucose is prepared into a 60 wt% modified glucose aqueous solution at 80°C, and the pre-irradiated low-density polyethylene powder is completely immersed in the solution for 1 hour, taken out and dried, and then completely immersed in a zinc salt solution. The mass ratio of zinc acetate to deionized water in the zinc salt solution is 3 g:40 mL. After soaking for 1 hour, the powder is taken out and dried;

[0055] The preparation method of the low-smoke halogen-free flame-retardant shipboard power cable material is as follows:

[0056] (1) Modified low-density polyethylene powder and urea are mixed uniformly in proportion, ground at 500 rpm for 15 min, 1 / 3 of the weight of antioxidant is added, and mixed uniformly to obtain an intermediate layer powder;

[0057] (2) 1 / 2 mass of graphene aerogel powder and 1 / 2 mass of molybdenum trioxide were mixed evenly, ground at 500 rpm for 15 min, and then 1 / 3 mass of antioxidant, 2 / 3 mass of polystyrene, 1 / 2 mass of lubricant, and 1 / 2 mass of high-density polyethylene powder were added in sequence and mixed thoroughly to obtain an upper layer of powder; the remaining materials were used to prepare a lower layer of powder according to the above process;

[0058] (3) The lower layer powder, the middle layer powder and the upper layer powder are loaded into the mold in order, and the three mixed powders are not mixed. The pressurization pressure is maintained at 15 MPa, and the temperature is first raised to 135 ° C, kept warm for 1 hour, then raised to 150 ° C, kept warm for 2 hours, and finally raised to 200 ° C, kept warm for 1 hour to obtain low smoke halogen-free flame retardant shipboard power cable material.

[0059] Comparative Example 1 (using glucose instead of modified glucose)

[0060] A low-smoke, halogen-free, flame-retardant shipboard power cable material, comprising, by weight, 100 parts of low-density polyethylene powder, 280 parts of high-density polyethylene powder, 20 parts of molybdenum trioxide, 5 parts of urea, 15 parts of an antioxidant, 80 parts of polystyrene powder, 5 parts of silicone oil, and 40 parts of graphene aerogel powder; the antioxidant is a combination of a natural olive phenol extract and antioxidant 168 in a weight ratio of 1:2; the polystyrene powder has a particle size of 213 μm, the low-density polyethylene powder has a particle size of 53 μm, and the high-density polyethylene powder has a particle size of 213 μm;

[0061] The preparation method of the low-density polyethylene powder comprises: pre-irradiating the low-density polyethylene powder with beta rays on an electron accelerator device in an air atmosphere at an irradiation dose of 5 kGy, preparing glucose into a 50 wt% glucose aqueous solution at 80° C., completely immersing the pre-irradiated low-density polyethylene powder in the solution for 1 hour, removing the powder from the solution and drying it, and then completely immersing the powder in a zinc salt solution in which the mass ratio of zinc acetate to deionized water is 0.5 g:40 mL, immersing the powder for 1 hour, and drying it;

[0062] The preparation method of the low-smoke halogen-free flame-retardant shipboard power cable material is as follows:

[0063] (1) Low-density polyethylene powder and urea are mixed uniformly in proportion, ground at 300 rpm for 10 min, 1 / 3 of the weight of antioxidant is added, and mixed uniformly to obtain an intermediate layer powder;

[0064] (2) 1 / 2 mass of graphene aerogel powder and 1 / 2 mass of molybdenum trioxide were mixed evenly, ground at 300 rpm for 10 min, and then 1 / 3 mass of antioxidant, 2 / 3 mass of polystyrene, 1 / 2 mass of lubricant, and 1 / 2 mass of high-density polyethylene powder were added in sequence and mixed thoroughly to obtain an upper layer of powder; the remaining materials were used to prepare a lower layer of powder according to the above process;

[0065] (3) The lower layer powder, the middle layer powder and the upper layer powder are loaded into the mold in order. The three mixed powders are not mixed. The pressurization pressure is maintained at 3 MPa. The temperature is first raised to 135 ° C and kept warm for 1 hour. Then the temperature is raised to 150 ° C and kept warm for 2 hours. Finally, the temperature is raised to 180 ° C and kept warm for 1 hour to obtain low-smoke halogen-free flame-retardant shipboard power cable material.

[0066] Comparative Example 2 (not immersed in zinc salt solution)

[0067] A low-smoke, halogen-free, flame-retardant shipboard power cable material, comprising, by weight, 100 parts of modified low-density polyethylene powder, 280 parts of high-density polyethylene powder, 20 parts of molybdenum trioxide, 5 parts of urea, 15 parts of an antioxidant, 80 parts of polystyrene powder, 5 parts of silicone oil, and 40 parts of graphene aerogel powder; the antioxidant is a combination of a natural olive phenol extract and antioxidant 168 in a weight ratio of 1:2; the polystyrene powder has a particle size of 213 μm, the low-density polyethylene powder has a particle size of 53 μm, and the high-density polyethylene powder has a particle size of 213 μm;

[0068] The preparation method of the modified low-density polyethylene is:

[0069] (1) 14 g of glucose and 50 mL of methanol were stirred at 65°C until completely dissolved, and then 1 g of 3-butene-1-amine and 0.1 mL of glacial acetic acid were added. The mixture was reacted for 2 h to precipitate a large amount of white precipitate. The precipitate was filtered and the filter cake was washed three times with anhydrous methanol and dried at 40°C for 12 h to obtain modified glucose.

[0070] (2) Pre-irradiating low-density polyethylene powder with β-rays in an electron accelerator device under air atmosphere with an irradiation dose of 5 kGy. A 50 wt% aqueous solution of modified glucose at 80° C. was prepared, and the pre-irradiated low-density polyethylene powder was completely immersed in the solution for 1 hour, and then taken out and dried.

[0071] The preparation method of the low-smoke halogen-free flame-retardant shipboard power cable material is as follows:

[0072] (1) Modified low-density polyethylene powder and urea are mixed uniformly in proportion, ground at 300 rpm for 10 min, 1 / 3 of the weight of antioxidant is added, and mixed uniformly to obtain an intermediate layer powder;

[0073] (2) 1 / 2 mass of graphene aerogel powder and 1 / 2 mass of molybdenum trioxide were mixed evenly, ground at 300 rpm for 10 min, and then 1 / 3 mass of antioxidant, 2 / 3 mass of polystyrene, 1 / 2 mass of lubricant, and 1 / 2 mass of high-density polyethylene powder were added in sequence and mixed thoroughly to obtain an upper layer of powder; the remaining materials were used to prepare a lower layer of powder according to the above process;

[0074] (3) The lower layer powder, the middle layer powder and the upper layer powder are loaded into the mold in order. The three mixed powders are not mixed. The pressurization pressure is maintained at 3 MPa. The temperature is first raised to 135 ° C and kept warm for 1 hour. Then the temperature is raised to 150 ° C and kept warm for 2 hours. Finally, the temperature is raised to 180 ° C and kept warm for 1 hour to obtain low-smoke halogen-free flame-retardant shipboard power cable material.

[0075] Comparative Example 3

[0076] A low-smoke, halogen-free, flame-retardant shipboard power cable material, comprising, by weight, 100 parts of low-density polyethylene powder, 280 parts of high-density polyethylene powder, 20 parts of molybdenum trioxide, 5 parts of urea, 15 parts of an antioxidant, 120 parts of polystyrene powder, 5 parts of silicone oil, and 40 parts of graphene aerogel powder; the antioxidant is a combination of a natural olive phenol extract and antioxidant 168 in a weight ratio of 1:2; the polystyrene powder has a particle size of 213 μm, the low-density polyethylene powder has a particle size of 53 μm, and the high-density polyethylene powder has a particle size of 213 μm;

[0077] The preparation method of the low-smoke halogen-free flame-retardant shipboard power cable material is as follows:

[0078] (1) 14 g of glucose and 50 mL of methanol were stirred at 65°C until completely dissolved, and then 1 g of 3-butene-1-amine and 0.1 mL of glacial acetic acid were added and reacted for 2 h. A large amount of white precipitate was precipitated, which was filtered and the filter cake was washed three times with anhydrous methanol and dried at 40°C for 12 h to obtain modified glucose. Low-density polyethylene powder, 20 parts of modified glucose, 10 parts of zinc acetate, and urea were mixed uniformly in proportion and ground at 300 rpm for 10 min. 1 / 3 of the weight of antioxidant was added and mixed uniformly to obtain an intermediate layer powder.

[0079] (2) 1 / 2 mass of graphene aerogel powder and 1 / 2 mass of molybdenum trioxide were mixed evenly, ground at 300 rpm for 10 min, and then 1 / 3 mass of antioxidant, 2 / 3 mass of polystyrene, 1 / 2 mass of lubricant, and 1 / 2 mass of high-density polyethylene powder were added in sequence and mixed thoroughly to obtain an upper layer of powder; the remaining materials were used to prepare a lower layer of powder according to the above process;

[0080] (3) The lower layer powder, the middle layer powder and the upper layer powder are loaded into the mold in order. The three mixed powders are not mixed. The pressurization pressure is maintained at 3 MPa. The temperature is first raised to 135 ° C and kept warm for 1 hour. Then the temperature is raised to 150 ° C and kept warm for 2 hours. Finally, the temperature is raised to 180 ° C and kept warm for 1 hour to obtain low-smoke halogen-free flame-retardant shipboard power cable material.

[0081] Comparative Example 4

[0082] The difference between Comparative Example 4 and Example 1 is that no polystyrene powder is added, and the remaining steps are the same as Example 1.

[0083] Comparative Example 5

[0084] The difference between Comparative Example 5 and Example 1 is that graphene aerogel powder is not added, and the remaining steps are the same as Example 1.

[0085] Comparative Example 6

[0086] A low-smoke, halogen-free, flame-retardant shipboard power cable material comprises, by weight, 100 parts of modified low-density polyethylene powder, 280 parts of high-density polyethylene powder, 20 parts of molybdenum trioxide, 5 parts of urea, 15 parts of an antioxidant, 80 parts of polystyrene powder, 5 parts of silicone oil, and 40 parts of graphene aerogel powder. The components are uniformly mixed and melt-extruded. The antioxidant is a combination of a natural olive phenol extract and antioxidant 168 in a weight ratio of 1:2. The polystyrene powder has a particle size of 213 μm, the low-density polyethylene powder has a particle size of 53 μm, and the high-density polyethylene powder has a particle size of 213 μm.

[0087] The preparation method of the modified low-density polyethylene is:

[0088] (1) 14 g of glucose and 50 mL of methanol were stirred at 65°C until completely dissolved, and then 1 g of 3-butene-1-amine and 0.1 mL of glacial acetic acid were added. The mixture was reacted for 2 h to precipitate a large amount of white precipitate. The precipitate was filtered and the filter cake was washed three times with anhydrous methanol and dried at 40°C for 12 h to obtain modified glucose.

[0089] (2) In an air atmosphere, low-density polyethylene powder is pre-irradiated with beta rays on an electron accelerator device with an irradiation dose of 5 kGy. Modified glucose is prepared into a 50 wt% modified glucose aqueous solution at 80°C, and the pre-irradiated low-density polyethylene powder is completely immersed in it. After soaking for 1 hour, it is taken out and dried, and then completely immersed in a zinc salt solution. The mass ratio of zinc acetate to deionized water in the zinc salt solution is 0.5 g:40 mL. After soaking for 1 hour, it is taken out and dried.

[0090] The measured results are shown in the following table:

[0091] Table 1

[0092]

[0093]

[0094] It can be seen from the above table that the cable material prepared in the embodiment of the present invention has stable and efficient flame retardant and smoke suppression properties, high mechanical strength, and excellent comprehensive performance, and has important application value in the field of cable material technology.

[0095] The upper and lower layers of the present invention are compounded with high-density polyethylene, polystyrene, and graphene aerogel. The combination of the three achieves both rigidity and flexibility - HDPE maintains toughness, PS enhances rigidity, and graphene further strengthens and optimizes the overall mechanical properties, ultimately obtaining a sheath material with excellent mechanical properties. The flame retardant mechanism dominated by graphene combined with the thermal insulation performance and barrier effect of aerogel can inhibit the escape of polystyrene decomposition products, and molybdenum trioxide is used to further optimize the flame retardant properties of the upper and lower layers.

[0096] The present invention utilizes modified glucose grafted onto low-density polyethylene, which is soaked in a zinc salt solution to form a complex, which is combined with a high-density polyethylene mixed powder as an intermediate layer and subjected to a pressurized heat treatment. The heat treatment causes the glucose to be thermally decomposed into carbon, and the zinc ions form zinc hydroxide that adheres to the carbon surface. This treatment method allows the zinc hydroxide / glucose-based carbon to be evenly dispersed in the polyethylene matrix, enhancing the mechanical properties of the material. At the same time, the interface defects between the filler and the matrix are reduced, and the interaction force is enhanced. In the event of a fire or high temperature, the zinc hydroxide decomposes and absorbs heat energy, reducing the temperature rise rate when the polyethylene cable material burns, slowing down the thermal decomposition and combustion process, forming a zinc oxide catalyst, and working together with the glucose-based carbon to make the carbon layer stronger and improve the flame retardant properties.

[0097] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the invention can be embodied in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as illustrative and non-restrictive, and the scope of the invention is defined by the appended claims, not the foregoing description, and all variations within the meaning and range of equivalents of the claims are intended to be encompassed therein. Any reference in a claim should not be construed as limiting the claim to which it relates.

Claims

1. A low-smoke, halogen-free, flame-retardant shipboard power cable material, comprising, by weight, 100-140 parts of modified low-density polyethylene powder, 280-340 parts of high-density polyethylene powder, 20-30 parts of molybdenum trioxide, 5-8 parts of urea, 15-30 parts of antioxidant, 80-120 parts of polystyrene powder, 5-8 parts of lubricant, and 40-60 parts of graphene aerogel powder, characterized in that: The preparation method of the modified low-density polyethylene is as follows: the low-density polyethylene is pre-irradiated, immersed in a modified glucose solution, taken out and dried, then immersed in a zinc salt solution, and taken out and dried.

2. The low-smoke, halogen-free, flame-retardant shipboard power cable material according to claim 1, characterized in that: The particle sizes of the polystyrene powder, low-density polyethylene powder and high-density polyethylene powder are 53 to 213 μm.

3. The low-smoke, halogen-free, flame-retardant shipboard power cable material according to claim 1, characterized in that: The specific steps of the pre-irradiation are: in an air atmosphere, the low-density polyethylene powder is pre-irradiated with beta rays on an electron accelerator device, with an irradiation dose of 5 kGy.

4. The low-smoke, halogen-free, flame-retardant shipboard power cable material according to claim 1, characterized in that: The preparation method of the modified glucose is as follows: 14-20 g of glucose and 50-60 mL of methanol are stirred at 65° C. to completely dissolve them, and then 1-5 g of 3-butene-1-amine and 0.1 mL of glacial acetic acid are added, reacted for 2 hours, a large amount of white precipitate is precipitated, filtered, and the filter cake is washed with anhydrous methanol three times and dried at 40° C. for 12 hours.

5. The low-smoke, halogen-free, flame-retardant shipboard power cable material according to claim 1, characterized in that: The lubricant is at least one of silicone oil, magnesium stearate, paraffin wax, and PE wax.

6. The low-smoke, halogen-free, flame-retardant shipboard power cable material according to claim 1, characterized in that: The modified glucose solution is a 50-60 wt% modified glucose aqueous solution at 80°C.

7. The low-smoke, halogen-free, flame-retardant shipboard power cable material according to claim 1, characterized in that: The antioxidant is obtained by combining natural olive phenol extract and antioxidant 168 in a weight ratio of 1:

2.

8. A method for preparing a low-smoke, halogen-free, flame-retardant marine power cable material, characterized in that: The method comprises the following preparation steps: (1) Modified low-density polyethylene powder and urea are mixed uniformly in proportion, ground at 300-500 rpm for 10-15 minutes, and 1 / 3 of the weight of antioxidant is added and mixed uniformly to obtain an intermediate layer powder; (2) 1 / 2 mass of graphene aerogel powder and 1 / 2 mass of molybdenum trioxide are mixed evenly, ground at 300-500 rpm for 10-15 min, and then 1 / 3 mass of antioxidant, 2 / 3 mass of polystyrene, 1 / 2 mass of lubricant, and 1 / 2 mass of high-density polyethylene powder are added in sequence and mixed thoroughly to obtain an upper layer of powder; the remaining materials are used to prepare a lower layer of powder according to the above process; (3) The lower layer powder, the middle layer powder and the upper layer powder are respectively loaded into the mold in order without mixing the three mixed powders, pressurized and sintered, and demolded to obtain low-smoke halogen-free flame-retardant marine power cable material.

9. The method for preparing a low-smoke, halogen-free, flame-retardant shipboard power cable material according to claim 1, characterized in that: The pressurized pressure in step (3) is 3-35 MPa, and the sintering temperature is: first heated to 135°C, kept warm for 1 hour, then heated to 150°C, kept warm for 2 hours, and finally heated to 180-200°C, kept warm for 1 hour.

Citation Information

Patent Citations

  • Preparation method of graphene aerogel powder and graphene aerogel powder

    CN108147401A